Does Corporate Social Responsibility enhance Corporate Reputation? An ethnographic case study on E.ON UK from an employee perspective. - Mathew, Justy (2007)
Clearing the aftermath of a series of high-profile scandals that have irreversibly changed the corporate landscape, we now live in a business world where perception is valued as much as performance and profit. (Hill & Knowlton, 2006, p.1)